P0063 HPV infection and lymphoma incidence using cervical conisation as a surrogate marker: A Danish nationwide cohort study. (July 2015) - Intaraphet, S.; Farkas, D. Körmendiné; Jóhannesdóttir, S. Alba; Cronin-Fenton, D.; Søgaard, M.
Abstract : Background: Persistent human papillomavirus (HPV) infection may promote carcinogenesis by hyperactivation of the immune system. We therefore explored the associations between HPV infection and risk of Hodgkin's and non-Hodgkin lymphoma in a nationwide cohort study using conisation as a surrogate marker. Methods: We identified all Danish women who underwent conisation between 1978 and 2011. We computed standardised incidence ratios and 95% confidence interval (CI) for Hodgkin's and non-Hodgkin lymphomas based on rates of national cancer incidence. Findings: Of 87, 435 women who underwent conisation (1978–2011), we noted an increased incidence of Hodgkin's lymphomas (standardised incidence ratio [SIR] 1.48, 95% CI 1.05–2.02), but only a slight increase in incidence for non-Hodgkin lymphoma (SIR 1.10, 95% CI 0.97–1.25). Interpretation: HPV infection, as measured by conisation, is associated with an increased risk of lymphoma. This association may be attributable to a chronic immune activation induced by persistent HPV infection or poor clearance of HPV.